Pengaruh social media marketing dan electronic word of mouth terhadap keputusan pembelian produk house of smith dengan brand image sebagai variabel intervening - devin arisena; Yofina Mulyati (New Economy, 2025)
This research examines the influence of social media marketing and electronic word of mouth (E- WOM) on the purchasing decisions of House of Smith Padang products, with brand image as an intervening variable. Using a quantitative approach, data were collected through questionnaires distributed to 120 respondents who have experience purchasing House of Smith products. The analysis was conducted using Partial Least Squares (PLS) to assess the direct and indirect relationships between the variables. The research results show that social media marketing has a positive and significant effect on purchasing decisions, and Electronic Word of Mouth has a positive and significant effect on purchasing decisions. Social media marketing and Electronic Word of Mouth have a positive and significant impact on brand image. brand image has a positive but not significant effect on purchase decisions. Brand image does not have a mediating effect between Social Media Marketing and Electronic Word of Mouth on Purchase Decisions.